O ensino religioso como possibilidade pedagógica à promoção de ações pela cultura de paz no campo educacional. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Given the legal insertion brought to the Law of Directives and Bases of National Education through Law No. 13663/2018, which states that educational institutions should promote actions for the Culture of Peace in the school environment, the question arose what would be the possible procedures to fulfill this norm. Thus, this work has as its main objective, to verify if Religious Education as an area of knowledge and part of the Common National Curricular Base can be considered a strategy capable of promoting the Culture of Peace in schools. For that, it was sought to study the central aspects about the Culture of Peace, Education for Peace, Religions and Religious Education, including their concepts, whose theoretical references are based on authors from interdisciplinary areas such as Education, Sociology, History and Law. From the choice of these four central aspects, some notions from the Complexity Theory were researched to set up a better understanding of the Culture of Peace and Education for Peace, especially the possibilities pointed out for resolving conflicts in a positive way. Each school is formed by a community that reflects its routine, its conflicts and the way of being and acting of the people who are in that place, integrating a community, a neighborhood or a city according to their own aspects such as culture, access to goods and services, violence, among others. Thus, the actions for the Culture of Peace cannot be the same for all schools, because they will vary according to the place where it is located. Next, we tried to get to know some religious theories established by philosophers, as well as the religious models existing in the world. For this, a convergence among the main religions in the world was sought, in order to verify the perspectives for the approximation of the Culture of Peace with Religious Education. From these, the interrelation with religious freedom and worldview, with religiosity, spirituality, and human values. Thus, we sought to discover clues about the possibility that secular Religious Education, as stated in the educational legislation in force, can be used to promote the Culture of Peace in the school environment. The methodology used was qualitative and exploratory research. Thus, after analyzing the theoretical reference covered, the Human Formation/Religious Education group of the elementary school of the Municipal Department of Education of the city of Ponta Grossa-PR was chosen for the field research. Data collection was made through semistructured interviews with educators connected to this group, with questions related to two themes: Culture of Peace and Religious Teaching/Spirituality. As results, among others, it was discovered the possibilities arising from the rescue of human values to bring a Culture of Peace to the school environment. The same values can be included in the Religious Education guidelines.
Keywords: Cultura de Paz; Educação para a Paz; Ensino Religioso; Escola; Religiões; Culture of Peace; Education for Peace; Religious Education; School; Religions; CNPQ::CIENCIAS SOCIAIS APLICADAS